Analisis Perbandingan Efisiensi Bank Umum Syariah Dan Bank Umum Konvensional Dengan MetodeData Evelopment Analysis (Dea) Periode 2010-2014 - Fitrianingsih, Norma; , Drs. Yuni Prihandi Utomo., MM; , Drs. Harun., MH (2017)
This research to knowing and analyze differences in the level of efficiency of Islamic Banks and Conventional Commercial Bank, using secondary data derived from the annual financial statements published on the 4 Islamic Banks (Bank muamalat, Bank Mandiri syariah, Bank BRI Syariah, Bank BNI Syariah) and 4 Conventional Commercial Bank (Bank Mandiri, Bank BRI, Bank BNI, Bank BTN) in the period 2010-2014. The data is analyzed using the methods Data Envelopment Analysis (DEA) with input oriented approach, to determine the level of efficiency at each bank. Based on the results of the study in 2010-2014 there are banks that have experienced inefficiency in the year 2010 is Bank BNI with Technical Efficiency for 0.932 and in 2012 at Bank Syariah Mandiri Technical Efficiency for 0.873. While in 2014 Islamic Banks and Conventional Commercial Bank made the object of research is already in a state of 100% efficiency. can be concluded that during the study period of 2010-2014 there was no difference between the efficiency of Islamic Banks and Conventional Commercial Bank.